Supporting and empowering people with epilepsy: Contribution of the Epilepsy Specialist Nurses (SENsE study) - Elliott, Naomi; Higgins, Agnes; Doherty, Colin (My University, 2019)
Purpose: To explore how Epilepsy Specialist Nurses in the Republic of Ireland enacted their clinical role. Methods: Qualitative descriptive design that involved individual and focus group interviews, observation and documentary analysis. Data were collected from 12 Epilepsy Specialist Nurses working in five hospital-based epilepsy services in Ireland, 24 multidisciplinary team members, and 35 people with epilepsy and their family members were involved. Data were analysed in NVivo using an inductive and deductive approach. Results: Epilepsy Specialist Nurses work out of a value base that gives primacy to collaboration. active participation, relationship-based care, and respect for the voices of PWE and family members. They are key players in empowering people to self-manage their illness, Core dimensions of their clinical role includes: performing a comprehensive assessment to inform care and treatment; providing person-centred education; monitoring the impact of care and treatment; providing education to family members and significant others; providing psychosocial care to optimise psychological wellness; co-ordinating care to enhance patients’ journey; and quality assuring patient information. Conclusion: Findings from this study highlight the key role ESNs played as members of the MDT in building and supporting PWE’s capacity to self-manage their illness. However, they also indicate deficits in the provision of information on sudden unexpected death in epilepsy and how to disclose a diagnosis of epilepsy by the ESN, as well deficits in their knowledge and confidence in supporting people experiencing significant mental health morbidities.
PUBLISHED
https://doi.org/10.1016/j.seizure.2019.06.008
Keywords: Epilepsy; Advanced practice; Nurse specialist; Clinical role; Self-management; Epilepsy